MORPHEME ANALYSIS OF ENGLISH LANGUAGE - Silvi Nuril Maulidia; Aisya Brilian; Mahuda Safitri; Rahmania Firdaus; Rama Garetha Evansam; Ahmad Siswanto (Universitas Islam Balitar, 2017)
Morphology is the study of words. Morphemes are the minimal units of words that have a meaning and can not be subdivided further. There are two main types: free and bound. Morpheme is article includes a listof references, but its sources remain unclear because it has insufficient.Therefore the researchers conducted the research about morpheme. The research methode that was used is decriptive qualitative method. To gain the data the researchers used literature review in which the data gained from dictionary. Every morpheme can be classified as either free or bound. Bound morphemes can be further classified as derivational or inflectional. These categories are mutually exclusive, and as such, a given morpheme will belong to exactly one of them. Free morphemes can function independently as words. Bound morphemes appear only as part us of words, always in conjunction with a root and sometimes with other bound morphemes.